Impact of Covid-19 Pandemic on the Financial Behavior - Gunawan, Ade; Koto, Murviana; Yusnandar, Willy; Jufrizen, Jufrizen (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The spread of Covid-19 in Indonesia has caused disruption in all sectors, including the economic sector. One of the economic sectors currently in the spotlight is the declining per capita income, while consumption must continue to run to meet daily life. The study aims to identify the financial behavior of Muhammadiyah people in Medan before and after the Covid-19 pandemic, especially in the aspects of consumption, cash flow management, saving, investment, and credit management. In addition, it measures whether there are differences in the financial behavior of Muhammadiyah people in Medan before and after the covid-19 pandemic, so that it can be a reference for what form of financial behavior should be. The impact of the Covid-19 pandemic is certainly a force majeure situation that can occur anytime and anywhere. Even though there are still many other force majeure events that can occur. It is a quantitative approach, with a statistically correlated parametric test (t test), if the data is not normal, then the Wilcoxon test is carried out. Based on the results of the study, it was found that there were significant differences between the financial behavior of Muhammadiyah people in Medan before and during the Covid-19 pandemic.